Kepuasan Memediasi Pengaruh Kualitas Sistem, Kualitas Informasi dan Pelatihan terhadap Kinerja Individual Pengguna Siskeudes - Aini, Hayyun; Irwan, M.; Surasni, Ni Ketut (E-Jurnal Akuntansi; Vol 31 No 9 (2021)DO - 10.24843/EJA.2021.v31.i09.p15, 2021)
This study aims  to  provide empirically the effect of system quality, information quality and training on performance as well as the effect of mediating satisfaction on the effect of system quality, information quality and training on the performance of village financial information system users (Siskeudes) in East Lombok Regency. The method used is explanatory research with a quantitative approach, with a sample of 71 village treasurers. The results showed that system quality, information quality and satisfaction had a positive and significant effect on performance and satisfaction partially mediated the effect of system quality, information quality and training on the performance of village financial information system users (SISKEUDES) in East Lombok Regency. Keywords: System Quality; Quality Of Information; Training; Satisfaction; Performance.